Violación y embarazo, una perspectiva desde el COIP - Surati Alvarado, Krystel Mayte (Machala : Universidad Técnica de Machala, 2023)
INTRODUCTION: Rape continues to be a public health problem in every nation, in Latin America the prevalence and incidence of rape against women is methodologically impossible to measure, but records are obtained where it is evident that a woman suffers within the last few years. twelve months incidences of abuse and rape, fulfilling an estimated age range with greater reception in women from 11 to 47 years of age, there is an iceberg between what is seen and what is recognized as a problem, eventually, as well as commitments and the resolutions that comply with each of the complaints requested by affected women. OBJECTIVE: To analyze rape and pregnancy from the perspective of the Comprehensive Criminal Organic Code (COIP) and its comparison with Latin American countries through the systematic analysis of scientific articles in order to guarantee correct learning in the face of this situation. METHODOLOGY: Narrative bibliographic study, based on the search for scientific articles by collecting updated information in scientific databases such as Google Scholar, Scielo, Pubmed, Science Direct, of the last 5 years. CONCLUSION: Of the Latin American countries, Ecuador has the highest sentence of deprivation of liberty, being the same as if there is a sexual violation due to threat and physical aggression, the sentence will be from 19 to 22 years and if the victim dies, the sentence increases. from 22 to 26 years old.
INTRODUCCION: La violación sexual sigue siendo un problema de salud pública de cada nación, en Latinoamérica la prevalencia e incidencia de violaciones en contra de las mujeres es metodológicamente imposible de medir pero se obtiene registros en donde se evidencia que una mujer sufre dentro de los últimos doce meses incidencias de maltrato y violaciones sexuales, cumpliendo un rango de edad estimada con mayor acogida en mujeres desde los 11 a 47 años de edad, existe un iceberg entre lo que se ve y lo que se reconoce como problema eventualmente así mismo como los compromisos y las resoluciones que acatan cada una de las denuncias solicitadas por mujeres afectadas. OBJETIVO: Analizar la violación y embarazo desde la perspectiva del Código orgánico integral penal (COIP) y su comparación con los países latinoamericanos mediante el análisis sistemático de artículos científicos con el fin de garantizar un correcto aprendizaje frente esta situación. METODOLOGIA: Estudio bibliográfico narrativo, basada en la búsqueda de artículos científicos mediante la recopilación de información actualizada en bases científicas como Google Académico, Scielo, Pubmed, Science Direct, de los últimos 5 años. CONCLUSION: De los países latinoamericanos Ecuador cuenta con la mayor pena de privación de libertad siendo la misma que si llega a existir una violación sexual por amenaza y agresión física la pena será de 19 a 22 años y si existe muerte de la víctima la pena aumenta de 22 a 26 años.
Keywords: VIOLACION; EMBARAZO; COIP; PAISES LATINOAMERICANOS